Brevipalpus yothersi Baker (Tenuipalpidae) development in sweet orange plants is influenced by previous mite infestation and the presence of shelters - Kapp, Ana Beatriz Piai [UNESP]; Vechia, Jaqueline Franciosi Della [UNESP]; Sinico, Thaís Elise; Bassanezi, Renato Beozzo; Ramos-González, Pedro Luis; Freitas-Astúa, Juliana; Andrade, Daniel Júnior [UNESP] (Springer Nature, 2024)
Citrus leprosis is the most important viral disease affecting citrus. The disease is caused predominantly by CiLV-C and is transmitted by Brevipalpus yothersi Baker mites. This study brings some insight into the colonization of B. yothersi in citrus [(Citrus × sinensis (L.) Osbeck (Rutaceae)] previously infested by viruliferous or non-viruliferous B. yothersi. It also assesses the putative role of shelters on the behavior of B. yothersi. Expression of PR1 and PR4 genes, markers of plant defense mechanisms, were evaluated by RT-qPCR to correlate the role of the plant hormonal changes during the tri-trophic virus-mite-plant interplay. A previous infestation with either non-viruliferous and viruliferous mites positively influenced oviposition and the number of adult individuals in the resulting populations. Mite populations were higher on branches that had received a previous mite infestation than branches that did not. There was an increase in the expression of PR4, a marker gene in the jasmonic acid (JA) pathway, in the treatment with non-viruliferous mites, indicating a response from the plant to their feeding. Conversely, an induced expression of PR1, a marker gene in the salicylic acid (SA) pathway, was observed mainly in the treatment with viruliferous mites, which suggests the activation of a plant response against the pathogen. The earlier mite infestation, as well as the presence of leprosis lesions and a gypsum mixture as artificial shelters, all fostered the growth of the B. yothersi populations after the second infestation, regardless of the presence or absence of CiLV-C. Furthermore, it is suggested that B. yothersi feeding actually induces the JA pathway in plants. At the same time, the CiLV-C represses the JA pathway and induces the SA pathway, which benefits the mite vector.
Keywords: Citrus leprosis mite; Citrus leprosis pathosystem; Citrus sinensis; Plant defense pathways